Carbothermal Methods: Highly Dispersed Copper Nanoparticles Supported on Activated Carbon as an Efficient Catalyst for Selective Reduction of Vanillin (Small 36/2018). Issue 36 (6th September 2018) - Fan, Ruoyu; Chen, Chun; Han, Miaomiao; Gong, Wanbing; Zhang, Haimin; Zhang, Yunxia; Zhao, Huijun; Wang, Guozhong
Abstract : In article number1801953, Chun Chen, Huijun Zhao, Guozhong Wang, and co‐workers synthesize a 15 wt%‐Cu/AC‐600 catalyst via a one‐pot carbothermal method at 600 °C, which yields highly dispersed copper nanoparticles supported on a carbon matrix, and consequently exhibits excellent catalytic activity and selectivity in the aqueous‐phase hydrodeoxygenation and organic‐phase (2‐propanol) transfer‐hydrogenation reaction of vanillin to 2‐methoxy‐4‐methylphenol.